Bedforms-ATM, an open source software to analyze the scale-based hierarchies and dimensionality of natural bed forms - Gutierrez, Ronald R. (2018)
Bedforms-ATM (Bed forms analysis toolkit for multiscale modeling) is a software designed to hierarchize and quantify the dimensionality of natural bed forms fields. It comprises four modular applications, namely: (1) wavelet analysis, (2) Hovmöller analysis, (3) multiscale discrimination, and (4) three-dimensionality analysis. Bedforms-ATM also provides insights on bed form systems dynamics and their interrelationship with the surrounding hydrodynamic characteristics. The software structure encourages its expandability via the collaboration from the community of users. Both fluvial and synthetic bed form data accompany Bedforms-ATM.